2013
DOI: 10.1152/ajpheart.00858.2012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial reactive oxygen species: which ROS signals cardioprotection?

Abstract: H874 -H882, 2008). The ROS responsible for this effect is not known. The present study focuses on superoxide (O 2 ·Ϫ ), hydrogen peroxide (H2O2), and hydroxyl radical (HO˙), each of which has been proposed as the signaling ROS. Feedback activation of mitoK ATP provides an ideal setting for studying endogenous ROS signaling. Respiring rat heart mitochondria were preincubated with ATP and diazoxide, together with an agent being tested for interference with this process, either by scavenging ROS or by blocking RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 48 publications
0
57
0
1
Order By: Relevance
“…Several molecular steps are activated, including extracellular regulated kinase 1/2, phosphatidylinositol 3 kinase/Akt, protein kinase C, and protein kinase G, which are able to inhibit glycogen synthase kinase-3 β and, in turn, the opening of the mitochondrial permeability transition pore [132]. Also mitochondrial ROS are consistently involved in the causative mechanisms of IP [133]. The protection induced by IP is not more operating after a few hours after the last cycle of ischemia/reperfusion but reappears 24 hours later.…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular steps are activated, including extracellular regulated kinase 1/2, phosphatidylinositol 3 kinase/Akt, protein kinase C, and protein kinase G, which are able to inhibit glycogen synthase kinase-3 β and, in turn, the opening of the mitochondrial permeability transition pore [132]. Also mitochondrial ROS are consistently involved in the causative mechanisms of IP [133]. The protection induced by IP is not more operating after a few hours after the last cycle of ischemia/reperfusion but reappears 24 hours later.…”
Section: Discussionmentioning
confidence: 99%
“…ROS can serve as signaling molecules and trigger signaling pathways involved in cell protection (Gibson, 2013). Over the past decade there is a growing body of evidence that confirms the participation of ROS in the phenomenon of preconditioning in muscle cells (Yellon et al, 2003;González et al, 2010;Garlid et al, 2013). This phenomenon was described for the first time by Murry et al, who demonstrated that the heart muscle could be protected from severe ischemic injury by pre-treatments with short-time ischemic periods (Murry et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…, Garlid et al . ) and plays a role in regulating cardiac function under physiological conditions (Perjes et al . ).…”
Section: Discussionmentioning
confidence: 99%